Pengaruh Environment Knowledge Dan Green Packaging Terhadap Green Repurchase Intention Dimediasi Green Trust - Selviana, Defi; Iqbal Daulay, M.Yasser (Universitas Islam Kadiri, 2023)
In 2022, the amount of waste available on the website (SIPSN) shows an accumulation of 35,953,862.11 tons of waste every year. Therefore, the aim of this research is to determine the influence of Environmental Knowledge and Environmentally Friendly Packaging on the intention to repurchase environmentally friendly products through Green Trust. Data was collected via an online questionnaire with a total of 210 respondents. Data analysis used Structural Equation Modeling (SEM) and SMART PLS software version 4.0. The research results state that environmental knowledge has a positive and significant effect on the level of consumer trust in the green environment. The use of Green Packaging also has a positive and significant impact on consumers' Green Trust levels. Green Trust has a positive and significant effect on Green Repurchase Intention. This research also states that Environmental Knowledge has a direct positive and significant effect on Green Repurchase Intention through the mediating role of the level of Green Trust. Apart from that, Green Packaging has a positive influence on Green Repurchase Intention through trust in Green Trust as an intermediary. Knowledge of the environment and the use of environmentally friendly packaging can encourage consumer confidence to repurchase Frisian Flag products.